A decade of photo‐identification reveals contrasting abundance and trends of Type B killer whales in the coastal waters of the Antarctic Peninsula. Issue 1 (8th July 2021) - Fearnbach, Holly; Durban, John W.; Ellifrit, David K.; Paredes, Alyssa; Hickmott, Leigh S.; Pitman, Robert L.
Abstract: The Antarctic Peninsula (AP) is rapidly warming and empirical data on abundance trends of marine organisms are required to understand the impact of these physical changes, and interacting anthropogenic impacts, on the ecosystem. Recent estimates inferred increasing abundance of Type A killer whales at the top of this food chain, and here we provide new data on the abundance of Type B1 and B2 killer whales using photographic mark‐recaptures collected during austral summers from 2008/2009 to 2017/2018. Both ecotypes were regularly photographed around the AP coastline, particularly off the west side, and individuals of both showed site fidelity across years. B1s had a higher re‐identification rate (58% photographed in multiple years, range: 1–7 years) compared to B2s (31%, 1–4 years). We fit mark‐recapture models that allowed temporary emigration beyond the study area, to effectively monitor the size of wide‐ranging populations and documented contrasting trends for B1s and B2s. A smaller population size (~102) of B1s was estimated to use the area, with a declining trend in abundance (−4.7% per year) and reduced apparent survival in recent years. In contrast, a much larger population size (~740) of B2s was estimated to be generally stable in abundance and apparent survival over the past decade.